(untitled) (American Journal of Business Management, Economics and Banking, 2023)
This article discusses the concept of digital economy, its role in management and its importance in achieving economic prosperity. Also, some statistical data obtained from open sources are presented, and based on them, an attempt is made to explain why the use of digital technologies is important. In addition, at the end of the article, an attempt is made to give an understanding of "artificial intelligence" and to shed light on why it is important.